2013
DOI: 10.1007/s10571-013-9926-7
|View full text |Cite
|
Sign up to set email alerts
|

Are Rod Outer Segment ATP-ase and ATP-Synthase Activity Expression of the Same Protein?

Abstract: Vertebrate retinal rod outer segments (OS) consist of a stack of disks surrounded by the plasma membrane, where phototransduction takes place. Energetic metabolism in rod OS remains obscure. Literature described a so-called Mg(2+)-dependent ATPase activity, while our previous results demonstrated the presence of oxidative phosphorylation (OXPHOS) in OS, sustained by an ATP synthetic activity. Here we propose that the OS ATPase and ATP synthase are the expression of the same protein, i.e., of F1Fo-ATP synthase.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 80 publications
(117 reference statements)
1
14
0
Order By: Relevance
“…IF1 specifically inhibits the ATP-hydrolyzing activity of the F1Fo-ATP synthase without impacting the synthesis of ATP during oxidative phosphorylation [17,18]. Elevated expression of IF1 has been observed in a number of human cancers [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…IF1 specifically inhibits the ATP-hydrolyzing activity of the F1Fo-ATP synthase without impacting the synthesis of ATP during oxidative phosphorylation [17,18]. Elevated expression of IF1 has been observed in a number of human cancers [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Having previously reported that ATP synthase and ATPase in the OS represent the same protein, that is the ectopic ATP synthase (Calzia et al ., ), ATPase activity was assayed in the presence of EGCG and quercetin to test their inhibitory action on OS ATP hydrolytic activity, as reported for mitochondrial ATP synthase (Zheng and Ramirez, ). As shown in Figure A and B, either compound exhibited concentration‐dependent inhibition of ATP hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, in the last few years, several Authors have reported the extramitochondrial functional expression of the OXPHOS machinery [reviewed in Panfoli et al., ], indicating that mitochondrial proteins are exportable. An extramitochondrial OXPHOS was reported in rod outer segment disks [Panfoli et al., , ; Calzia et al., ], myelin sheath from both central and peripheral nervous system [Ravera et al., , , , , ,b], plasma membrane of glioma C6 cells [Ravera et al., ] and lung adenocarcinoma cells [Chang et al., ]. These data are supported by several proteomic analyses [reviewed in Panfoli et al., ].…”
Section: Introductionmentioning
confidence: 83%